False‐positive hepatitis C virus serology after placement of a ventricular assistance device. Issue 1 (30th January 2016) - Durand, C.M.; Marr, K.A.; Ostrander, D.; Subramanian, A.; Valsamakis, A.; Cox, A.; Neofytos, D.
Abstract: Background: Ventricular assist devices (VADs) have been associated with immune activation and sensitization. We observed several cases of false‐positive (FP) hepatitis C virus (HCV) antibody (Ab) tests in patients being evaluated for orthotopic heart transplant (OHT), prompting us to investigate this further. Methods: We reviewed all VAD and OHT cases at Johns Hopkins from 2005 to 2012. FP HCV serology was defined as an equivocal or low‐positive HCV Ab, plus either (i) a negative recombinant immunoblot (RIBA) and/or HCV nucleic acid test (NAT), or (ii) an indeterminate RIBA and negative NAT. Results: In 53 patients with available HCV testing, nearly 40% of patients (21/53: 39.6%) developed FP HCV Ab tests after VAD placement: 4 patients had negative NAT, 12 had negative RIBA, and 5 had an indeterminate RIBA and negative NAT. All patients with indeterminate RIBA tests had isolated reactivity to the same HCV protein, c100p/5‐1‐1p (NS4b protein). In 3 of 4 VAD patients who had OHT and repeat HCV Ab testing after VAD removal, repeat HCV Ab was negative (699–947 days after OHT); in 1 case, FP HCV serology persisted (5 days after OHT). Thirteen patients had OHT alone and none developed a FP HCV Ab. Conclusions: FP HCV Ab results following VAD placement are very common. Reversal of FP serology in several patients after VAD removal is suggestive of a possible association with the VAD hardware. Clinicians should be aware of this phenomenon, as it could lead to delays in determining eligibility for OHT and increased costs.